Consensus statement on the definition of neurogenic supine hypertension in cardiovascular autonomic failure by the American Autonomic Society (AAS) and the European Federation of Autonomic Societies (EFAS) : Endorsed by the European Academy of Neurology (EAN) and the European Society of Hypertension (ESH) - Fanciulli, Alessandra; Jordan, Jens; Biaggioni, Italo; Calandra-Buonaura, Giovanna; Cheshire, William P.; Cortelli, Pietro; Eschlboeck, Sabine; Grassi, Guido; Hilz, Max-Josef; Kaufmann, Horacio; Lahrmann, Heinz; Mancia, Giuseppe; et al. (Clinical Autonomic Research, 2018)
PURPOSE: Patients suffering from cardiovascular autonomic failure often develop neurogenic supine hypertension (nSH), i.e., high blood pressure (BP) in the supine position, which falls in the upright position owing to impaired autonomic regulation. A committee was formed to reach consensus among experts on the definition and diagnosis of nSH in the context of cardiovascular autonomic failure. METHODS: As a first and preparatory step, a systematic search of PubMed-indexed literature on nSH up to January 2017 was performed. Available evidence derived from this search was discussed in a consensus expert round table meeting in Innsbruck on February 16, 2017. Statements originating from this meeting were further discussed by representatives of the American Autonomic Society and the European Federation of Autonomic Societies and are summarized in the document presented here. The final version received the endorsement of the European Academy of Neurology and the European Society of Hypertension. RESULTS: In patients with neurogenic orthostatic hypotension, nSH is defined as systolic BP ≥ 140 mmHg and/or diastolic BP ≥ 90 mmHg, measured after at least 5 min of rest in the supine position. Three severity degrees are recommended: mild, moderate and severe. nSH may also be present during nocturnal sleep, with reduced-dipping, non-dipping or rising nocturnal BP profiles with respect to mean daytime BP values. Home BP monitoring and 24-h-ambulatory BP monitoring provide relevant information for a customized clinical management. CONCLUSIONS: The establishment of expert-based criteria to define nSH should standardize diagnosis and allow a better understanding of its epidemiology, prognosis and, ultimately, treatment.
EVALuna2:213464